Effects of dietary copper, zinc, and ractopamine hydrochloride on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria - Feldpausch, J. A.; Amachawadi, Raghavendra G.; Tokach, Michael D.; Scott, H. M.; Nagaraja, Tiruvoor G.; Dritz, Steven S.; Goodband, Robert D.; Woodworth, Jason C.; DeRouchey, Joel M. (My University, 2017)
A total of 480 pigs (PIC 327 × 1050; initially 48.7 ± 2.3 kg) were used to determine the interactive effects of supplemental Cu, Zn, and ractopamine HCl (RAC) on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria. Treatments were arranged in a 2 × 2 × 2 factorial with the main effects of added Cu (CuSO4; 0 vs. 125 mg/kg Cu), Zn (ZnO; 0 vs. 150 mg/kg Zn), and RAC (0 vs. 10 mg/kg during the last 28 d prior to marketing). All diets contained 11 mg/kg Cu and 73 mg/ kg Zn from the trace mineral premix. Pens of pigs were balanced and blocked on initial BW and then randomly allotted to 1 of the 4 mineral treatment diets. At 28 d prior to marketing, pens within each block and mineral treatment were randomly assigned to receive either 0 or 10 mg/kg RAC in addition to the mineral treatment. Adding either Cu or Zn alone did not improve ADG or ADFI yet resulted in numerical improvements in overall G:F and caloric efficiencies, but improvements were not additive (Cu × Zn, P = 0.057, P = 0.068, and P = 0.064 for G:F and caloric efficiency on a ME and NE basis, respectively). Ractopamine improved (P < 0.001) overall ADG, G:F, and caloric efficiency, thereby increasing final BW by 3% with no change in ADFI. Ractopamine also increased (P < 0.001) HCW, percentage carcass yield, G:F, loin depth, and percent fat-free lean and decreased (P = 0.014) backfat. Adding Zn or Cu alone to diets containing RAC numerically improved percent yield and HCW G:F, but this effect was absent when the Cu or Zn was added to the control diet or when Cu and Zn were fed in combination in RAC diets (Cu × Zn × RAC, P = 0.011 and P = 0.018 for yield and HCW G:F, respectively). Fecal samples were collected on d 0 and at the conclusion of the finishing period (d 90) for bacterial isolation and antimicrobial susceptibility determinations according to Clinical and Laboratory Standards Institute minimal inhibitory concentrations breakpoints. Enterococcus spp. and Escherichia coli isolates displayed varying levels of resistance to certain antibiotics prior to initiation of treatments on d 0. Resistance to most antibiotics decreased (P < 0.05) over time or was stable for those that had a low baseline percentage of resistance. Neither Zn nor RAC adversely affected antimicrobial resistance. However, extended feeding of 125 mg/kg Cu throughout the finishing period seems to decrease enterococcal susceptability to tetracycline, tylosin, and quinupristin/dalfopristin. © 2016 American Society of Animal Science. All rights reserved.
Citation: Feldpausch, J. A., Amachawadi, R. G., Tokach, M. D., Scott, H. M., Nagaraja, T. G., Dritz, S. S., . . . DeRouchey, J. M. (2016). Effects of dietary copper, zinc, and ractopamine hydrochloride on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria. Journal of Animal Science, 94(8), 3278-3293. doi:10.2527/jas2016-0340
Keywords: Antimicrobial Resistance; Enteric Bacteria; Finishing Pig; Growth Performance